An analysis of the socioeconomic and environmental benefits of wind energy deployment in Europe. (November 2020) - Ortega-Izquierdo, Margarita; Río, Pablo del
Abstract: The penetration of renewable energy sources for electricity generation is critical to decarbonize electricity systems, a main goal in the context of the energy transition. Among renewable energies capacity additions, wind energy has played a dominant role in the European Union and elsewhere, fuelled by technology cost reductions and public promotion schemes. In turn, wind deployment has led to considerable socioeconomic and environmental benefits in terms of CO2 emissions reductions, avoidance of fossil fuels and employment creation. The aim of this paper is to assess those socioeconomic and environmental benefits of wind energy deployment in the European Union and their evolution over time. Based on two novel methodologies, which allow a disaggregated analysis per country and stage of the supply chain (only for employment creation), an ex-post calculation of those benefits over the 2008–2016 period has been carried out. Our results show that, overall, those benefits are considerable and have increased over time. However, some benefits are more relevant than others. In fact, the monetary calculation of the fossil fuel savings is twice the benefits in terms of CO2 emissions abatement. Their relevance also differs across countries and, for employment creation, across distinct stages of the value chain. Highlights: Ex-post calculation of the benefits of wind energy in the EU in the period 2008–2016. Assessment of the emission reductions, avoidance of fossil fuels and employment creation. The monetary quantification of the fossil fuel savings is twice the benefits of CO2 emissions abatement. More than 2.5 million jobs created in the period 2008–2016 in the EU28. Policy costs are higher than benefits from CO2 and fossil fuel reductions.